Efektifitas Terapi Murottal Al-Qur’an Surah Ar-Rahman dalam Menstabilkan Status Hemodinamik Pasien Cerebrovascular Accident di Ruang ICU - Nandira Aisya Alifia Muhtadi; Indri Wahyuningsih (Journal of Innovative and Creativity, 2025)
The study purpose was to evaluate the effectiveness of murottal Al-Quran Surah Ar-Rahman therapy in stabilizing the hemodynamic status of a patient with cerebrovascular accident (CVA) admitted to the Intensive Care Unit (ICU). Stroke remains one of the leading causes of global morbidity and mortality, with a 70% increase in incidence from 1990 to 2021. Optimal hemodynamic stability, reflected by parameters such as blood pressure, pulse, respiration, oxygen saturation, and mean arterial pressure (MAP), is essential for preventing secondary brain injury. Non-pharmacological interventions, such as spiritual auditory stimulation, have shown potential in supporting physiological recovery. This qualitative case study employed a pre–post test design involving one CVA patient, identified as NY J, aged 50 years, in the ICU. The intervention consisted of murottal therapy of Surah Ar-Rahman for three consecutive days, with each session lasting 16 minutes. Data were collected through non-invasive monitoring of vital signs, family interviews, and medical documentation to evaluate changes in hemodynamic parameters before and after the intervention. Findings revealed marked hemodynamic improvement following the therapy. Blood pressure decreased from 224/127 mmHg (day 1 pre-test) to 176/110 mmHg (day 3 post-test), pulse rate dropped from 111 bpm to 90 bpm, respiratory rate stabilized at 20 bpm, oxygen saturation increased to 99%, and MAP improved from 156 mmHg to 132 mmHg. These results indicate enhanced cardiovascular stability and parasympathetic activation. Murottal Surah Ar-Rahman therapy effectively contributes to hemodynamic stabilization in ICU CVA patients through relaxation mechanisms that support parasympathetic activity. This finding aligns with prior evidence highlighting the therapeutic role of spiritual auditory interventions in critical care.